2007
DOI: 10.1007/s00216-007-1244-9
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of intracellular pH change induced by drug stimulation using silica nanoparticle sensors

Abstract: We have synthesized and applied a nanoparticle-based pH sensor for noninvasive monitoring of intracellular pH changes induced by drug stimulation. The pH sensor is a two-fluorophore-doped nanoparticle sensor (2DFNS) that contains a pH-sensitive indicator (fluorescein isothiocyanate, FITC) and a reference dye (tris(2,2'-bipyridyl)dichlororuthenium(II) hexahydrate, RuBPY). The nanoparticles have an average diameter of 42 +/- 3 nm and can easily be taken up by cells for noninvasive intracellular pH measurement. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
112
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 126 publications
(114 citation statements)
references
References 31 publications
2
112
0
Order By: Relevance
“…In this case the pH sensor is composed of a shell of covalently bound indicator-dye molecules surrounding a core of sequestered, covalently bound, reference-dye molecules. What is interesting is that although both authors used covalent immobilization, Peng et al, 2007, reported an extensive dye leakage.…”
Section: Advances In Chemical Sensorsmentioning
confidence: 98%
See 3 more Smart Citations
“…In this case the pH sensor is composed of a shell of covalently bound indicator-dye molecules surrounding a core of sequestered, covalently bound, reference-dye molecules. What is interesting is that although both authors used covalent immobilization, Peng et al, 2007, reported an extensive dye leakage.…”
Section: Advances In Chemical Sensorsmentioning
confidence: 98%
“…In the field of biology and medicine, sensors able to monitor pH in real time are in great demand, as they can be used for the general understanding of biological processes and for biomedical diagnostics (Doussineau et al, 2009). Recently, a lot of work has been done on optical pH-sensitive micro- (Borisov et al, 2008a;Doussineau et al, 2009;Schulz et al, 2009 ;Hornig et al, 2008) and nano-sensors (Allard & Larpent, 2008;Burns et al, 2006;Gao et al, 2005;Gao et al, 2007;Kim et al, 2006;Peng et al, 2007;Sun et al, 2006;). Here, the latter will be discussed, since they are less than 100 nm in size.…”
Section: Nanosensors For Phmentioning
confidence: 99%
See 2 more Smart Citations
“…monodisperse dye-doped silica nanoparticles capable of noninvasive insertion into living cells. [35][36][37] Compartmented two-dye nanosensors have been described, allowing quantitative real-time pH monitoring based on the principle of ratiometric measurements. By placing a pH-insensitive reference dye in the silica core and a pH-indicator dye in the shell, such sensor systems circumvent problems associated with intensity-based measurements, i.e., dependence on the probe concentration or fluctuations in the light source intensity.…”
Section: Introductionmentioning
confidence: 99%